Nanostructure-assisted drought tolerance in olive trees (Olea europaea L.): the role of Fe2O3-graphitic carbon - Gholami, Rahmatollah; Fahadi Hoveizeh, Narjes; Zahedi, Seyed Morteza; Padervand, Mohsen; Dawi, Elmuez A.; Carillo, Petronia (Frontiers in Plant Science, 2024)
Olive trees are known as one of the most iconic crops in the world. Considering the increasing water deficit worldwide, implementing some profitable and empirical strategies can be inevitable upon exposure to drought stress. Therefore, the present study aimed at clarifying the beneficial role of exogenously foliar application of Fe2O3 modified carbon nitride nanostructures (control, FeSO4, C3N4 and Fe2O3/g-C3N4) to "Shengeh" olive cultivars grown at different watering levels (100, 75, and 50% ET) in two experimental years (2022 and 2023) and the pomological attributes, physiological and biochemical changes happening in the treated leaves and fruits were discussed. The results indicated that drought stress caused a significant decline in pomological attributes in this experiment, and treatments could remarkably make up for this damage. Overall, Fe2O3/g-C3N4 outperformed as compared FeSO4 and C3N4 alone, which were also efficacious in conferring tolerance to the water deficit stress. Conversely, severe drought stressed-olive fruits showed higher oil content percent in the fresh matter and water use efficiency (WUE) in oil by 30% and 52.5%, respectively, as an average of results of two years, and after Fe2O3/g-C3N4, these features in olive plants subjected to severe drought improved by an average of 35% over two years. Ca2+ and K+ in olive plants under severe drought stress declined by 50% and 83% in 2022 and 46% and 24% in 2023, while Na+ increased in the plants exposed to 50%ET stress by 48% and 57% in two successive experimental years respectively. The application of Fe2O3/g-C3N4 remarkably improved the contents of Ca2+ and K+ by 101.5% and 369%, respectively, as an average of two years. Conversely, this beneficial treatment led to a significant decline in Na+ levels by 30% in 2022 and 2% in 2023 under stressful conditions. Moreover, it decreased the ‘osmolytes’ content, caused a smaller decline in chlorophyll levels, and resulted in higher relative water content occurring in the treated olive leaves. The reduction of oxidative markers was a result of the increased enzymatic activity after the use of Fe2O3/g-C3N4. Therefore, this treatment is a promising strategy to achieve improved resistance in olive plants in the future.